Factors Influencing the Firm Performance of Digital Merchandising Businesses in Thailand - Siriyotha , Sirisart; Lekcharoen , Somchai (Journal of Ecohumanism, 2024)
Thailand’s national strategy focuses on making the country more competitive by helping modern entrepreneurs succeed both within the country and internationally. This research aims for development a new framework that shows how critical elements like market capabilities, IT capabilities, digitalization, and innovation contribute to the success of digital businesses in Thailand. The study uses a mixed method research, combining an integration of qualitative and quantitative techniques are utilized. Within qualitative research, we gathering insights from 20 experts, by using e-Rough Set Delphi method. In quantitative research, The research was based on a collection of 611 valid datasets, which were gathered from digital merchandising business owners in Thailand via online questionnaires. The results indicate that market capabilities, IT capabilities, digitalization, and innovation all have an influential and meaningful effect on business performance. Research also emphasizes importance of investing in IT infrastructure, adopting advanced IT strategies, and improving market capabilities to stay competitive in the fast-changing digital market. The insights from this study are valuable for strengthening the digital economy, as adopting digital technologies and innovations can help businesses grow sustainably and positively impact the overall economy and society.